2021
DOI: 10.25115/psye.v13i3.5586
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de estrategias de afrontamiento efectivas para reducir el acoso escolar y su impacto en las víctimas estables

Abstract: El acoso escolar provoca graves efectos en quienes se ven implicados, especialmente en las víctimas. Entre ellas, aquellas que viven estos episodios de forma prolongada son quienes manifiestan más consecuencias negativas. Para luchar contra este problema, el alumnado pone en marcha diferentes estrategias de afrontamiento que les permiten detener o sobrellevar estas situaciones y mitigar sus efectos. Este estudio pretende analizar el impacto del programa Asegúrate en las estrategias de afrontamiento usadas por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Studies analysing coping styles have found that seeking social support is one of the most effective (Chan & Wong, 2017;Cho & Yoo, 2017;Mora-Merchán et al, 2021;Perren et al, 2012). Such coping not only curbs cyberaggressions, but also buffers adverse effects such as depression, anxiety, and lowered self-esteem through the support of others (Machackova et al, 2013;Na et al, 2015;Raskauskas & Huynh, 2015;Völlink et al, 2013;Worsley et al, 2018).…”
Section: Coping Effectively With Cyberbullying: Seeking Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies analysing coping styles have found that seeking social support is one of the most effective (Chan & Wong, 2017;Cho & Yoo, 2017;Mora-Merchán et al, 2021;Perren et al, 2012). Such coping not only curbs cyberaggressions, but also buffers adverse effects such as depression, anxiety, and lowered self-esteem through the support of others (Machackova et al, 2013;Na et al, 2015;Raskauskas & Huynh, 2015;Völlink et al, 2013;Worsley et al, 2018).…”
Section: Coping Effectively With Cyberbullying: Seeking Social Supportmentioning
confidence: 99%
“…In turn, this would help cybervictims, especially girls, recognise that it is possible to overcome this negative situation, especially if they feel well-supported (Chen & Zhu, 2021;Na et al, 2015;Worsley et al, 2018). Given the similarities regarding the difficulty of coping with face-to-face aggression, such interventions could also promote social support seeking among those dealing with school bullying (Chan & Wong, 2017;Mora-Merchán et al, 2021). Such prevention and intervention strategies must be designed and implemented from a whole-school perspective (i.e., in collaboration with parents, students, teachers, and other professionals); cybervictims should be actively supported to enhance emotional and instrumental resources.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…Los resultados encontrados deberán ser confirmados en futuros estudios en contextos menos estresantes e inciertos que los generados durante el confinamiento. Estos resultados también resaltan el papel de la resiliencia como característica personal relevante en la gestión de situaciones complejas como la cibervictimización de rumores, siendo un componente importante que habrá de ser considerado en el diseño de programas contra el ciberacoso en los que los escolares puedan aprender estrategias de afrontamiento que les permitan detener o sobrellevar estas situaciones y mitigar sus efectos (Mora-Merchán et al, 2021).…”
Section: Discussionunclassified
“…The findings have important implications for intervention since they highlight the need to incorporate content related to romantic competencies (Davila et al, 2009) and intervene at an early age to prevent this phenomenon, to which some adolescents are exposed in an ongoing, stable manner. This information is especially relevant since these adolescents show greater resistance to change (Mora-Merchán et al, 2021). Adolescent boys and girls need to learn to identify aggressive behaviors in their romantic relationships, not only in relation to face-to-face aggression, but also in terms of abuse perpetrated using technological means.…”
Section: Discussionmentioning
confidence: 99%